Human Limitations to Introduction of Smart Cities: Comparative Analysis From Two CEE Cities - Daniel KLIMOVSKÝ; Uroš PINTERIČ; Diana ŠAPARNIENĖ (Transylvanian Review of Administrative Sciences, 2016)
Abstract Smart cities are a modern administrative/ developmental concept that tries to combine the development of urban areas with a higher level of citizens’ participation. However, there is a lack of understanding of the concept’s potential, due possibly to an unwillingness to accept a new form of relationship with the citizens. In this article, the willingness to introduce the elements of smart cities into two Central and Eastern European cities is tested. The results show that people are reluctant to use technology above the level of their needs and show little interest in participating in matters of governance, which prevents smart cities from developing in reality.